Towards Building Cyberphysical Systems with Agile Architecture - Alexander Vodyaho; Nataly Zhukova; Yulia Schichkina; Saddam Abbas; Vladimir Chernokulsky (Journal of Computer Networks and Communications)
The current stage of technology development is characterized by an increase in the complexity of the created anthropogenic systems, a constant expansion of the scope of information technologies, an increase in the intelligence level of the created systems, and the appearance of new paradigms for building information-oriented systems such as cyber-physical systems, the Internet of things, and cloud and fog systems. Modern information-oriented systems very often have dynamic structure, implement complex adaptive behavior, and can be considered as systems with agile architecture. The article discusses one of the possible approaches for building cyberphysical systems with agile architecture on fog platforms. The idea of the proposed approach is to accumulate knowledge about the current state of the observed cyberphysical systems in the form of knowledge graphs. As a model, it is proposed to use multilevel relatively finite state operating automaton at the upper level and knowledge graphs at the lower level. A distinctive feature of the developed approach is that models that describe the current state of the observed system can be built automatically.